2019
DOI: 10.1002/chem.201805526
|View full text |Cite
|
Sign up to set email alerts
|

Zinc‐Mediated Intermolecular Reductive Radical Fluoroalkylsulfination of Unsaturated Carbon–Carbon Bonds with Fluoroalkyl Bromides and Sulfur Dioxide

Abstract: A versatile and general zinc‐mediated intermolecular reductive radical fluoroalkylsulfination of unsaturated C−C bonds has been developed using readily available fluoroalkyl bromides and 1,4‐diazabicyclo[2.2.2]octane‐bis(sulfur dioxide) adduct (DABSO) with wide substrate scope and excellent functional group tolerance. Sulfur dioxide anion radical generated in situ from the reduction of sulfur dioxide with zinc may be involved in the reaction mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 102 publications
0
13
0
Order By: Relevance
“…Interestingly, the cross-coupling product 3 was obtained in 51% yield when the reactions were carried out under standard reaction conditions. These result may indicate that the in situ-generated Mn­(I) would coordinate with the olefin to accelerate the radical addition reaction …”
Section: Resultsmentioning
confidence: 53%
“…Interestingly, the cross-coupling product 3 was obtained in 51% yield when the reactions were carried out under standard reaction conditions. These result may indicate that the in situ-generated Mn­(I) would coordinate with the olefin to accelerate the radical addition reaction …”
Section: Resultsmentioning
confidence: 53%
“…[116][117][118] In 2019, Chen and coworkers achieved a zinc-mediated intermolecular reductive radical fluoroalkylsulfination of unsaturated C-C bonds with fluoroalkyl bromides and DABSO (Scheme 47). 119 Alkenes and alkynes were all tolerated in this reaction, affording the product with moderate yields. Preliminary mechanistic investigations revealed that a sulfur dioxide anion radical species reduced by Zn from SO 2 was involved in this reaction.…”
Section: Scheme 38mentioning
confidence: 90%
“…In addition, the fluoroalkyl group to be introduced is limited to the CF 3 group because of structural limitations of the above-mentioned precursor. More recently, external addition of a SO 2 source such as bis­(sulfur dioxide)–1,4-diazabicyclo[2.2.2]­octane adduct (DABSO) has extended accessible fluoroalkyl groups and alkenes in addition to the CF 3 group and aliphatic alkenes, but this is not an atom-economical strategy . During preparation of the present Letter, the Liao group reported an electrochemical method for cascade-type trifluoromethyl-sulfonylation of N -cyanamide alkenes with 1a .…”
mentioning
confidence: 92%